Hate Speech on Tiktok: A Forensic Linguistic Study - Yasser M. H. Ahmed Alrefaee; Gumarpi Rahis Pasaribu (JELIM : Journal of Education, Language, Social and Management, 2025)
This study investigates the linguistic and sociolinguistic characteristics of hate speech on TikTok, focusing on how language is used to target and marginalize specific social groups. Drawing on a dataset of user comments, the analysis identifies recurring linguistic strategies such as dehumanization, stereotyping, imperative speech acts, and threats of violence. These expressions are not isolated utterances but socially constructed acts of symbolic violence, reflecting broader ideologies of power, exclusion, and prejudice. Using the frameworks of van Dijk’s ideological discourse analysis and Bourdieu’s theory of symbolic violence, the study reveals how hate speech functions to reinforce social hierarchies in digital spaces. From a forensic linguistic perspective, the study also highlights the evidentiary potential of online comments for identifying speaker intent and legal violations. Furthermore, the platform’s design—marked by anonymity and algorithmic virality—facilitates the rapid spread of harmful language. The findings underscore the urgent need for ethical digital governance and critical media literacy to counter the normalization of hate speech online.